Educational Organization and Administration; Educational Administration: Theory, Research, and Practice; Contemporary Educational Administration - William E. Sparkman (Educational Considerations, 1983)
Book reviews of: Educational Organization and Administration, by Edgar L. Morphet, Roe L. Johns and Theodore L. Reller Educational Administration: Theory, Research, and Practice, by Wayne K. Hoy and Cecil G. Miskel Contemporary Educational Administration, by William G. Monahan and Herbert R. Hengst.